Design and development of experimental model of regenerative braking system - Rasheed, Mohsin (040263) 2008 (Islamabad. Department of Mechatronics (Air University Main Campus), 2008)
When driving a car, a great amount of kinetic energy is lost when braking, making start up fairly strenuous. The goal of our project was to develop a system that stores the energy which is normally lost during braking, and reuses it. When brakes apply the motor that drives the car becomes a generator (the torque that is given to the motor now produce the electricity) when the armature is driven mechanically while surrounded by a magnetic field. While it$1 (Bs quite a feat of computer programming, the same control unit that operates the permanent-magnet DC motor handles the regenerative braking. Braking starts when deactivates the accelerator paddle and is applied more aggressively when press the brake paddle.s
BEMTS